MIAT: A pivotal oncogenic long noncoding RNA tunning the hallmarks of solid malignancies - Monica M. Rostom; Alaa A. Rashwan; Christina D. Sotiropoulou; Sama Z. Hozayen; Abdelhamid M. Abdelhamid; Miriam Mokhtar Abdelhalim; Omar Eltahtawy; Hadir M. Emara; Noha M. Elemam; Christos K. Kontos; Rana A. Youness (Translational Oncology)
Long non-coding RNAs (LncRNAs) have emerged as intriguing players in cellular regulation, challenging the traditional view of non-coding RNAs as mere ''dark genome''. Non-coding DNA makes up most of the human genome and plays a pivotal role in cancer development. These RNA molecules, which do not code for proteins, have captivated researchers with their diverse and crucial roles in gene regulation, chromatin dynamics, and other cellular processes. In several physiological and pathological circumstances, lncRNAs serve critical functions. This review will tackle the complex function of the lncRNA myocardial infarction-associated transcript (MIAT) in various solid malignancies. A special emphasis would be directed on the correlation between cancer patients' clinicopathological features and the expression profile of MIAT. MIAT is a oncogenic regulator in many malignant tumors, where it can control the growth, invasion, metastasis, and resistance to death of cells. As a result, MIAT is thought to be a possible biomarker and therapeutic target for cancer patients. The biological functions, mechanisms and potential clinical implications of MIAT during carcinogenesis and finally the current possible therapeutic approaches targeting MIAT are also outlined in this review.